Cervicolumbar Coordination in Mammalian Quadrupedal Locomotion: Role of Spinal Thoracic Circuitry and Limb Sensory Inputs - Juvin, Laurent (J Neurosci, 2012)
Effective quadrupedal locomotion requires a close coordination between the spatially distant central pattern generators (CPGs) controlling forelimb and hindlimb movements. Using isolated preparations of the neonatal rat spinal cord, we explore the role of intervening thoracic circuitry in cervicolumbar CPG coordination and the contribution to this remote coupling of limb somatosensory inputs. In preparations activated with bath-applied N-methyl-d,l-aspartate, serotonin, and dopamine, the coordination between locomotor-related bursts recorded in cervical and lumbar ventral roots was substantially weakened, although not abolished, when the thoracic segments were selectively withheld from neurochemical stimulation or were exposed to a low Ca(2+) solution to block synaptic transmission. Moreover, cervicolumbar CPG coordination was reduced after a thoracic midsagittal section, suggesting that cross-cord projections participate in the anteroposterior coupling. In quiescent preparations, either cyclic or tonic electrical stimulation of low-threshold afferent pathways in C8 or L2 dorsal roots (DRs) could elicit coordinated ventral root bursting at both cervical and lumbar levels via an activation of the underlying CPG networks. When lumbar rhythmogenesis was prevented by local synaptic transmission blockade, L2 DR stimulation could still drive left–right alternating cervical bursting in preparations otherwise exposed to normal bathing medium. In contrast, when the cervical generators were selectively blocked, C8 DR stimulation was unable to activate the lumbar CPGs. Thus, in the newborn rat, anteroposterior limb coordination relies on active burst generation within midcord thoracic circuitry that additionally conveys ascending and weaker descending coupling influences of distant limb proprioceptive inputs to the cervical and lumbar generators, respectively.